2018
DOI: 10.21303/2504-5695.2018.00555
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Influence of “Amaranth” Cryoadditive on Organoleptic and Microbiological Parameters of Processed Cheeses

Abstract: There was grounded the expedience of using "Amaranth" cryoadditive in the technology of processed cheeses. "Amaranth" cryoadditive contains necessary vitamins and microelements of the natural origin. The use of "Amaranth" cryopowder in the processed cheeses technology allows to enrich them with vitamins, mineral substances and food fibers. The main factors of introducing "Amaranth" cryoadditive were: the normative organoleptic estimation of a product and its daily need. Introduction of "Amaranth" cryopowder in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(25 reference statements)
0
2
0
1
Order By: Relevance
“…Materials and methods applied in the course of present study are described in more detail in paper [22].…”
Section: Materials and Methods Of Researchmentioning
confidence: 99%
“…Materials and methods applied in the course of present study are described in more detail in paper [22].…”
Section: Materials and Methods Of Researchmentioning
confidence: 99%
“…Забезпечення населення високоякісними продуктами тваринництва -одне з найважливіших завдань працівників аграрного сектору України, які вкладають величезну творчу енергію та значні кошти для максимального забезпечення населення молоком і молочними продуктами (Ha et al, 2015;Yukalo and Datsyshyn, 2017;Kitchenko, 2017;Bilyk et al, 2017;Hachak et al, 2018).…”
Section: вступunclassified
“…It was found that it had an in-The main principles of creating new cheeses with a combined composition are to reduce calorie content and increase the content of biologically active substances. Such products must have a high taste and have a functional purpose [8].…”
Section: Introductionmentioning
confidence: 99%